Brain proton magnetic resonance spectroscopy findings in a Beagle dog with genetically confirmed Lafora disease - Neringa Alisauskaite; Katrin Beckmann; Matthias Dennler; Niklaus Zölch (Journal of Veterinary Internal Medicine, 2020)
Abstract Cortical atrophy has been identified using magnetic resonance imaging (MRI) in humans and dogs with Lafora disease (LD). In humans, proton magnetic resonance spectroscopy (1HMRS) of the brain indicates decreased N‐acetyl‐aspartate (NAA) relative to other brain metabolites. Brain 1HMRS findings in dogs with LD are lacking. A 6‐year‐old female Beagle was presented with a history of a single generalized tonic‐clonic seizure and episodic reflex myoclonus. Clinical, hematological, and neurological examination findings and 3‐Tesla MRI of the brain were unremarkable. Brain 1HMRS with voxel positioning in the thalamus was performed in the affected Beagle. It identified decreased amounts of NAA, glutamate‐glutamine complex, and increased total choline and phosphoethanolamine relative to water and total creatine compared with the reference range in healthy control Beagles. A subsequent genetic test confirmed LD. Abnormalities in 1HMRS despite lack of changes with conventional MRI were identified in a dog with LD.